2019
DOI: 10.1002/hyp.13373
|View full text |Cite
|
Sign up to set email alerts
|

Streamwater ages in nested, seasonally cold Canadian watersheds

Abstract: The mean transit time (MTT) is an important descriptor of water storage and release dynamics in watersheds. Although MTT studies are numerous for many regions around the world, they are rare for prairie watersheds where seasonally cold or dry conditions require adequate methodological choices towards MTT estimation, especially regarding the handling of sparse data records and tracer selection. To examine the impact of such choices, we used timeseries of δ 18 O and δ 2 H from two contrasted years (2014 and 2015… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 71 publications
5
31
1
Order By: Relevance
“…Although all three water age metrics produced the same youngest and oldest water sites for and δ 18 O data results, DR produced a similar but not exact ranking to MTT and Fyw. This agrees with non‐urban studies that found that all three water age metrics produce the comparable results and water age ranks (e.g., Bansah & Ali, ; Kirchner, ). These results demonstrate that although DR is a useful tool to perform a quick estimation of MTT, Fyw estimations better align with MTT estimations when using either δ 2 H or δ 18 O data in urbanizing catchments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although all three water age metrics produced the same youngest and oldest water sites for and δ 18 O data results, DR produced a similar but not exact ranking to MTT and Fyw. This agrees with non‐urban studies that found that all three water age metrics produce the comparable results and water age ranks (e.g., Bansah & Ali, ; Kirchner, ). These results demonstrate that although DR is a useful tool to perform a quick estimation of MTT, Fyw estimations better align with MTT estimations when using either δ 2 H or δ 18 O data in urbanizing catchments.…”
Section: Discussionsupporting
confidence: 90%
“…The water age computations were applied using the δ 18 O and δ 2 H tracers at each sample location. The DR (Equation ) uses the damping of precipitation isotope signals in stream flow to characterize general trends and distributions of MTT (Bansah & Ali, ; Soulsby et al, ; Tetzlaff et al, ): italicDR=CV of δ18Oor δ2H0.25emitalicin stream flowCV of δ18Oor δ2H0.25emitalicin precipitation, where CV represents the coefficient of variation.…”
Section: Methodsmentioning
confidence: 99%
“…We used a relatively long (>5 years) isotopic time series in this study, albeit at a relatively coarse (~weekly) resolution to characterize water ages. It is well known that travel time distributions are nonstationary and vary with hydroclimatological conditions, whereby wetter conditions (e.g., annually, seasonally, or even on an event basis) are typically associated with shorter MTTs and younger water (Harman, ; Peralta‐Tapia et al, ; Segura, James, Lazzati, & Roulet, ) and larger young water fractions (Bansah & Ali, ; Remondi, Kirchner, Burlando, & Fatichi, ). Moreover, despite our efforts to sample higher flows, the relatively coarse sampling resolution could be under‐representing some important short‐term processes (Aubert & Breuer, ; Birkel et al, ; Cayuela, Latron, Geris, & Llorens, ), especially as MTTs are short (Timbe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bansah and Ali () carried out a study to examine streamwater ages and mean transit times (MTT) in nested, seasonally cold Canadian Prairie watersheds using stable isotopes of water sources from two contrasting years. Results showed that most outlets in 2014 had young water fractions larger than 50% and MTT values <6 months.…”
mentioning
confidence: 99%
“…However, the location of the trench is an important consideration, with trenching higher in the basin and in flat terrain contributing more to baseflow, suggesting that this should be considered in Andean landscape and water resources management. Bansah and Ali (2019) carried out a study to examine streamwater ages and mean transit times (MTT) in nested, seasonally cold Canadian Prairie watersheds using stable isotopes of water sources from two contrasting years. Results showed that most outlets in 2014 had young water fractions larger than 50% and MTT values <6 months.…”
mentioning
confidence: 99%